Effect of machining parameters on surface roughness while turning metal matrix composites-an experimental approach. (2018) - Prakash Rao, C.R.; Bhagyashekar, M.S.; Chandra, P.; Ravikumar, D.V.
Abstract: Metal Matrix Composites (MMC's) reinforced with silicon carbide are preferred for automobile, aviation and marine application owing to its strength to weight ratio however these parts requires turning operation. The turning operation is intended to convert raw materials in to the final output having the desired quality in terms of component dimension and surface roughness. The desired quality of the components can be obtained by proper selection of parameters during turning MMCs. Hence present research paper is aimed at the study of the surface roughness while turning MMC's using CGGN120304 style, K10 grade uncoated tungsten carbide inserts. The cutting speed selected was 300m/min, 450m/min and 600m/min, feed of 0.08 mm/revolution, 0.16 mm/revolution, 0.24 mm/revolution and constant radial depth of cut of 1.5 mm. Experiments were conducted following ISO3685 standards. The Surface roughness was measured using SJ201P surface roughness measuring equipment. The experimental results revealed that while turning composites, Surface roughness were found lower when 600 m/min and 0.08 mm/revolution were used for machining. The cutting edges were subjected to high BUE at 0.08 mm/rev at all cutting speeds.